Dynamics and characterization of carbapenemase-producing Enterobacterales isolated from clinical specimens in a private healthcare center in Lima, Peru, from 2018 to 2019 - Ortiz-Gómez, Tamin; Barrón-Pastor, Heli; Tamariz, Jesús; Loyola, Steev (The Journal of Infection in Developing Countries, 2026)
Introduction: Antimicrobial resistance is a major and growing concern worldwide. The study aimed to describe the occurrence and characterize the antimicrobial resistance profile of carbapenemase-producing Enterobacterales (CPE) isolated from clinical specimens at a private healthcare center in Lima, Peru, between January 2018 and December 2019. Methodology: A total of 59 bacterial isolates were identified as CPE using the modified carbapenem inactivation method. Bacterial identification and antimicrobial susceptibility testing were performed using the Vitek 2 system, and colistin susceptibility was determined using the compact antimicrobial susceptibility panel. Five carbapenemase encoding genes, including blaNDM, blaIMP, blaVIM, blaOXA-48, and blaKPC, were screened using PCR and lateral flow assay. Also, carbapenemases were screened using the boronic acid- and EDTA-based disk synergy methods. The dynamics of CPE were described every month. Results: Carbapenemase-producing Klebsiella pneumoniae was the most prevalent agent (83.1%), followed by Providencia spp. (6.8%), Escherichia coli (5.1%), Enterobacter cloacae (3.4%), and Citrobacter freundii (1.6%). The isolation of blaNDM-carrying CPE was frequent and increased during the second half of 2019, while blaKPC carriers were detected in the second half of 2018. One CPE carrying blaOXA-48 was detected in June 2019. No other carbapenemase-encoding genes were detected. Conclusions: This report is among the first to document CPE in private health care institutions in Lima, Peru. Results suggest that the emergence and spread of carbapenemases are becoming a latent and growing threat in private healthcare settings.